Experimental Investigation into Failure Modes of Low-Yield-Point Steel Plate Shear Walls - Qinglan Liu; Jianhua Shao; Baijie Tang; Zhanguang Wang (Applied Sciences, 2022)
Two specimens of low-yield-point steel plate shear walls used for the experimental investigation into different failure modes of the structure were respectively carried out by the horizontal and vertical loading tests in this paper. The results derived from the horizontal loading test for specimen 1 demonstrated that both the infill panel and the frame column were seriously damaged as the loading level increased with continuous and steady strain growth, in which maximum out-of-plane displacement and strain of the infill panel reached 31.8 mm and 11,735 με respectively, whereas the strain of the frame column reached 13,117 με. Moreover, the structural bearing capacity decreased extremely slowly and the specimen still had a high strength when the controlled displacement of the specimen exceeded 3.28 times the yield displacement, which indicated that the ductility of the structure was excellent. The results of a vertical loading experiment for specimen 2 indicated that the maximum deformation of both the infill panel and frame column occurred in the middle-upper part of the members, with a maximum out-of-plane displacement of 95 mm and 70 mm, respectively. The dramatic out-of-plane bulging phenomenon along the width of the infill plate under the vertical load and the seriously torsional deformation of the frame column were observed.